2011
DOI: 10.1177/0022034511424283
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin Enhances Saliva IgA Response and Protection of Anti-caries DNA Vaccine

Abstract: We and others have shown that anti-caries DNA vaccines, including pGJA-P/VAX, are promising for preventing dental caries. However, challenges remain because of the low immunogenicity of DNA vaccines. In this study, we used recombinant flagellin protein derived from Salmonella (FliC) as a mucosal adjuvant for anti-caries DNA vaccine (pGJA-P/VAX) and analyzed the effects of FliC protein on the serum PAc-specific IgG and saliva PAc-specific IgA antibody responses, the colonization of Streptococcus mutans (S. muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 30 publications
0
30
0
9
Order By: Relevance
“…This group demonstrated chitosan could increase salivary IgA antibody responses as adjuvants to a DNA vaccine of pGJA-P/VAX [12]. We sought to further enhance salivary IgA and serum IgG antibody responses by including Salmonella-derived flagellin protein at the time of pGJA-P/VAX administration [11,20]. We found that recombinant flagellin protein as a mucosal adjuvant for anti-caries DNA vaccine pGJA-P/VAX via intranasal immunization can increase serum PAc-specific IgG and saliva PAc-specific IgA antibody responses as compared with pGJA-P/VAX alone and significantly decrease the colonization of S. mutans on rat teeth.…”
Section: Enhancement Of Specific Anti-caries Salivary Siga Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This group demonstrated chitosan could increase salivary IgA antibody responses as adjuvants to a DNA vaccine of pGJA-P/VAX [12]. We sought to further enhance salivary IgA and serum IgG antibody responses by including Salmonella-derived flagellin protein at the time of pGJA-P/VAX administration [11,20]. We found that recombinant flagellin protein as a mucosal adjuvant for anti-caries DNA vaccine pGJA-P/VAX via intranasal immunization can increase serum PAc-specific IgG and saliva PAc-specific IgA antibody responses as compared with pGJA-P/VAX alone and significantly decrease the colonization of S. mutans on rat teeth.…”
Section: Enhancement Of Specific Anti-caries Salivary Siga Antibodiesmentioning
confidence: 99%
“…More importantly, flagellin protein as a mucosal adjuvant promoted the ability of pGJA-P/VAX to reduce caries lesions, providing effective protection against dental caries. It is demonstrated that recombinant flagellin protein as a mucosal adjuvant for intranasal caries DNA vaccine enhanced saliva IgA response and conferred better protection against caries [20].…”
Section: Enhancement Of Specific Anti-caries Salivary Siga Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Recently, alternatives that might offer the possibility for efficient reduction of cariogenic microorganisms and, consequently, make a feasible control of dental caries are being sought. [18][19][20][21] Under these circumstances, photodynamic therapy (PDT) may be a possible new approach for caries treatment.…”
mentioning
confidence: 99%
“…Efforts have been made to develop antibacterial dental materials to combat bacteria and secondary caries. Several bioactive agents have been synthesized and incorporated into dental materials [Cheng et al, , 2013Huang et al, 2012;Shi et al, 2012], including various quaternary ammonium monomers (QAMs) that demonstrate favorable antibacterial properties.…”
Section: Evaluation Of Novel Anticaries Adhesive In a Secondary Cariementioning
confidence: 99%